2008
DOI: 10.1097/hjh.0b013e3282f314f7
|View full text |Cite
|
Sign up to set email alerts
|

A new oscillometric method for assessment of arterial stiffness: comparison with tonometric and piezo-electronic methods

Abstract: The Arteriograph is a new, easy-to-use and time-effective method for assessing arterial stiffness and wave reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
217
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(233 citation statements)
references
References 24 publications
8
217
2
6
Order By: Relevance
“…10 First studies showed a good agreement between parameters obtained oscillometrically (Arteriograph) and those obtained by standard techniques, including SphygmoCor and Complior. 5,6 In the present study, we found that the wave reflection parameter AI shows a good agreement between all methods, which has been previously shown for SphygmoCor and Arteriograph, 5 and is a novel finding for the Vascular Explorer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…10 First studies showed a good agreement between parameters obtained oscillometrically (Arteriograph) and those obtained by standard techniques, including SphygmoCor and Complior. 5,6 In the present study, we found that the wave reflection parameter AI shows a good agreement between all methods, which has been previously shown for SphygmoCor and Arteriograph, 5 and is a novel finding for the Vascular Explorer.…”
Section: Discussionsupporting
confidence: 87%
“…1 New devices, including the Arteriograph and the Vascular Explorer, have been developed to determine PWV, AI and central blood pressure from oscillometrically recorded brachial pressure waves using an upper arm cuff. 5,6 Because arterial stiffness parameters are determined from that single pressure pulse recording at the brachial artery, these new devices eliminate the intrusive procedure of obtaining a femoral pulse recording, and hence, offer the possibility of taking measurements in the sitting position. Measurements in the sitting position (ideally together with blood pressure measurements) could facilitate the use of arterial stiffness parameters in clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In a previous work, including more than 1000 children and teenagers, we provided reference values for pulse wave velocity (PWV), thereby constituting a suitable tool for longitudinal clinical studies assessing subgroups of children who are at long-term risk of cardiovascular disease. 10 A multitude of various methods and techniques have been used to assess PWV in adults such as applanation tonometry, 11,12 ultrasound, 13,14 methods using mechanotransducers 15 and computerized oscillometry; 16 furthermore, a number of comparative studies with diverging results have been published concerning the comparability of the different methods. [17][18][19][20][21] Instruments based on the principle of applanation tonometry (PulsePen (PP) (DiaTecne, Milan, Italy) and Sphygmocor (SC) (AtCor, Sydney, Australia) have been extensively used.…”
Section: Introductionmentioning
confidence: 99%
“…Augmentation index was normalized to a heart rate of 75 bpm (AIx@75) for comparison for different heart rates. 3,18 Statistical analysis Statistical analyses were carried out using the Statistical Package for Social Sciences for Windows, version 17 (SPSS Inc., Chicago, IL, USA). Kolmogorov-Smirnov test was used to determine the normality of the variables' distribu- 11.4%, respectively.…”
Section: Arterial Stiffness Measurementmentioning
confidence: 99%